2019
DOI: 10.1590/s1517-707620190004.0807
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation study of TiO2 and ZnO in suspension using miniaturized tests

Abstract: Miniaturization has been a trend in the instrumentation of chemical analyzes. The interest in miniaturization stems from the perceived benefits of faster, easier, less expensive and less wasteful analyzes than the tradition analyses. Thus, this work proposes a miniaturization of photocatalytic tests using a microplate reader for the analysis of several results, using only microliters of solution. The present work investigates the heterogeneous photocatalysis of the eosin yellow, acid yellow 73 and basic yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…Examination of this figure indicates that UV oxidation resulted in 27.43% dye degradation, compared to 45.95% for UV-ZnO NPs catalyzed process. This agrees with the work of Cambrussi et al [26].…”
Section: Effect Of Presence Of Catalystsupporting
confidence: 94%
“…Examination of this figure indicates that UV oxidation resulted in 27.43% dye degradation, compared to 45.95% for UV-ZnO NPs catalyzed process. This agrees with the work of Cambrussi et al [26].…”
Section: Effect Of Presence Of Catalystsupporting
confidence: 94%
“…During the analysis of specialized literature worldwide regarding the depth dependence of photoreaction rates, studies were found on the depth dependence of methylmercury photodecomposition in coastal and oceanic waters [37], photolysis on soil surfaces [38], and the Beer-Lambert law was mentioned [14,[39][40][41][42][43]. However, nothing was mentioned regarding the current study.…”
Section: Dependence Of the Reaction Rate On The Depthmentioning
confidence: 84%
“…3,7,8 According to some reports, ZnO outperforms TiO 2 and other semiconductor oxides of photocatalytic activity, which is determined by the ability to absorb solar radiation. [9][10][11] Two primary issues that limit ZnO from being utilized as a photocatalyst are its wide bandgap energy and the rapid recombination of electron pairs and photogenerated holes. Metal doping is one remediation method involving transition metals such as Mn, Co, Fe, Cu, Mg, and Ta, [12][13][14][15][16][17] and rare earth elements such as Er, Sm, La, Ce, Pr, Er, Yb into ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…3,7,8 According to some reports, ZnO outperforms TiO 2 and other semiconductor oxides of photocatalytic activity, which is determined by the ability to absorb solar radiation. 9–11…”
Section: Introductionmentioning
confidence: 99%